Protective Ventilation Strategies in Abdominal Surgery. (July 2014) - Proffitt, Adrian; Johnston, Andrew McD
Adoption of a Lung-Protective Ventilation Strategy (PEEP and Low Tidal Volume) in Patients Undergoing Abdominal Surgery is Associated with a Reduction in Pulmonary and Extra-Pulmonary Complications.